استخدام نظام المراقبة والتحكم وتحصيل المعطيات (SCADA) في إدارة مولد ديزل - الشامي إبراهيم; البستاني حسن; ملحم محمد (Latakia University Journal -Engineering Sciences Series, 2019)
Supervisory Control And Data Acquisition (SCADA) systems have been developed to reduce costs by optimizing plant operations. They allow wide monitoring and remote control from a central location. SCADA system is widely used in critical infrastructures such as electrical grid, natural gas, petroleum fields, wastewater industries, and other public infrastructure systems. SCADA system provides monitoring, data analysis, and control of equipment. In this paper, we present the technologies for data collection, data storage, and reporting in SCADA System. We also show and how these systems manage time by giving an overview of a SCADA system architecture and the functions it performs. Then, we discuss a practical implementation of a SCADA system taken from AL-ZARA Thermal Power Station. وجدت نظم المراقبة والتحكم وتحصيل المعطيات (SCADA) من أجل خفض الكلفة عن طريق أمثلة العمليات في المنشأة الصناعية، بالإضافة إلى أن هذه النظم تعطي إمكانية المراقبة الواسعة والتحكم عن بعد من موقع مراقبة مركزي. كذلك تستخدم نظم SCADA بشكل واسع في إدارة البنى التحتية العملية كشبكات الكهرباء، والغاز الطبيعي، و حقول النفط و المياه الصناعية، وغيرها من البنى الأساسية، وكذلك تؤمن جمع وتحليل المعطيات والتحكم بالمعدات. سنقدم من خلال هذه الدراسة شرحاً لتكنولوجيا تحصيل المعطيات وطريقة تخزينها و تحليل المعلومات و تشكيل التقارير في نظم SCADA، كما سنوضح كيف تقوم هذه النظم بإدارة الوقت، من خلال شرح البنية الأساسية لنظم SCADA، والوظائف التي تقوم بها، ومن ثم سوف نطرح تطبيقاً عملياً لنظام SCADA مأخوذاً من محطة التوليد الكهربائية في الزارة.